Aspectos técnicos e operacionais do uso de microturbinas conectadas aos sistmas elétricos para geração distribuída de energia - Costa, Dreifus Medeiros (2010)
The considerable increase in energy demand has increased the interest in reducing costs, improving reliability, quality and stability of power generation systems. The connection of distributed generation (DG) can be used as a strategic element to improve the voltage levels in power system. Microturbines (MT) have certain advantages over other models of GD, such as the possibility of using various types of fuels. This thesis analyzes the main considerations that should be observed in the use of microturbines as a form of DG. At first is analyze the basic characteristics of a microturbine such as its operation cycle, fuel type, efficiency and modeling. To connect the microturbine to the distribution network is adopted a three-phase rectifier with a power factor regulation and a hybrid multilevel inverter. The three-phase rectifier hold interface synchronous generator between the MT and the high voltage cell of the multilevel inverter. The multilevel inverter operates with asymmetrical voltage in their cells. In each of its cells can be inserted energy sources such as fuel cells, photovoltaic panels and wind generators. For this work is adopted a multilevel inverter with voltage ratios (1:3:9). At higher voltage module will be inserted into the microturbine. In the other two subsequent modules is adopted fixed voltage which later could be replaced by some alternative sources of energy